Catalyst for synthesizing 3-methyl-3-butene-1-alcohol as well as preparation and application of catalyst
The preparation of a catalyst for a three-dimensional rectangular mesh skeleton structure through 3D printing technology has solved the problems of difficulty in separation of existing catalysts and low strength, achieving higher mechanical strength and higher formaldehyde conversion and selectivity.
Patent Information
- Application Number
- CN202311460033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2043-11-03
AI Technical Summary
The existing catalysts that use isobutene and formaldehyde to form 3-methyl-3-butene-1-ol have difficulties in separation or low strength of molding catalysts, which are difficult to meet the requirements of liquid-solid separation in continuous production.
3D printing technology is used to prepare a catalyst for a three-dimensional rectangular mesh skeleton structure. By controlling the composition and proportion of the printing slurry, the mechanical strength and porosity of the catalyst are improved and the separation ability from the raw material products is enhanced.
It significantly improves the mechanical strength and service life of the catalyst, enhances the formaldehyde conversion rate and the selectivity of 3-methyl-3-butene-1-ol, and simplifies the separation process between raw materials and products.
Smart Images

Figure CN119926492A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solid base catalysis, and in particular to a catalyst for synthesizing 3-methyl-3-butene-1-ol and a preparation method and application thereof. Background Art
[0002] The chemical name of isopentenol is 3-methyl-2-butenol. It is an important organic intermediate that can be used to produce a variety of fine chemical products and medicines such as citral, floral fragrances and vitamin A. The traditional method for producing isopentenol is mainly the isoprene method, that is, isoprene is used as a raw material and is obtained through oxidation, acetification, alkaline solution saponification and other processes. This method has a long process route, a large amount of raw material consumption, a large number of by-products, a relatively high production cost and serious pollution.
[0003] In recent years, the method of preparing isopentenol from 3-methyl-3-butene-1-ol with isobutylene and formaldehyde as raw materials has become a research hotspot. The method has a simple process flow, few by-products, abundant raw material sources, low production cost and basically no pollution, so it has great development prospects. CN109317212A discloses a catalyst for synthesizing 3-methyl-3-butene-1-ol and its preparation method and use. The catalyst is composed of an amine compound and a strong base compound supported by a metal silicate modified by attapulgite. CN111068754A discloses a modified molecular sieve catalyst for 3-methyl-3-butene-1-ol and its preparation method. The catalyst uses a molecular sieve as a matrix, adopts water vapor, acid washing treatment, and alkaline phosphate composite modification, and can be used in the reaction of synthesizing 3-methyl-3-butene-1-ol from isobutylene and formaldehyde. CN107930686A discloses a synthesis method, catalyst and preparation method of 3-methyl-3-butene-1-ol. The preparation method of the catalyst for synthesizing 3-methyl-3-butene-1-ol includes: calcining the phosphorus silicon aluminum molecular sieve at 300-600°C for 3.5-5h, isocratically impregnating the molecular sieve in an alkaline phosphate solution, aging, drying, and calcining. However, the above catalyst is generally unformed powder or the formed catalyst particles are not strong enough to meet the requirements of liquid-solid separation in continuous production.
[0004] In summary, the existing catalysts for generating 3-methyl-3-butene-1-ol from isobutylene and formaldehyde generally have problems such as difficulty in separation (powdered catalysts or homogeneous catalysts) or low strength of formed catalysts. Therefore, providing a catalyst with higher strength, less prone to breakage, and easier to separate from the raw material product has become one of the problems to be solved by those skilled in the art. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a catalyst for synthesizing 3-methyl-3-butene-1-ol and its preparation and application. The catalyst of the present invention is applied to the reaction of isobutylene and formaldehyde to generate 3-methyl-3-butene-1-ol, has higher mechanical strength, can further extend the service life of the catalyst, and is easy to separate from the reaction raw materials and products, and can greatly improve the formaldehyde conversion rate and 3-methyl-3-butene-1-ol selectivity.
[0006] The first aspect of the present invention provides a method for preparing a catalyst for synthesizing 3-methyl-3-butene-1-ol, comprising:
[0007] (S1) mixing acrylic acid, acrylate, dispersant, leveling agent and photocuring agent to obtain a photosensitive resin mixed solution;
[0008] (S2) mixing the first powder and the photosensitive resin mixed solution obtained in step (S1), adding a suspending agent, a first foaming agent and a second powder in sequence, letting the mixture stand, and then adding an anti-sticking agent and a second foaming agent to obtain a printing slurry;
[0009] (S3) loading the printing slurry obtained in step (S2) into a liquid carrier, performing 3D printing according to a set program, and post-processing to obtain the catalyst.
[0010] Furthermore, in step (S1), the weight ratio of each substance in the mixed solution is: 20-32 parts of acrylic acid: 8-20 parts of acrylate: 2-10 parts of dispersant: 1.5-7.5 parts of leveling agent: 0.2-2 parts of photocuring agent.
[0011] Further, in step (S1), the acrylate is one or more of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, dipentaerythritol hexaacrylate, ditripropylene glycol diacrylate, trimethylolpropane triacrylate or ethoxylated trimethylolpropane triacrylate, preferably one or more of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate or trimethylolpropane triacrylate, and further preferably includes both dipropylene glycol diacrylate and trimethylolpropane triacrylate, wherein the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is preferably 1-2.5:1-1.5.
[0012] Furthermore, in step (S1), the dispersant is one or both of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, preferably 3-glycidyloxypropyltrimethoxysilane.
[0013] Furthermore, in step (S1), the rheological agent is one or both of polydimethylsiloxane and polymethylsiloxane, preferably polydimethylsiloxane.
[0014] Further, in step (S1), the photocuring agent is one or both of a photosensitizer or a photoinitiator, preferably including both a photosensitizer and a photoinitiator, wherein the weight ratio of the photosensitizer to the photoinitiator is preferably 1:10-1:100. Further, the photosensitizer is one or more of ethyl 4-dimethylaminobenzoate, triethylamine, ethyl-p-dimethylaminobenzoate or triethanolamine, preferably one or more of triethylamine or triethanolamine; the photoinitiator is one or more of 2-isopropylthioxanthone, methyl o-benzoylbenzoate, 2,4-diethylthioxanthone or 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methyl-1-propanone, preferably one or more of 2-isopropylthioxanthone or methyl o-benzoylbenzoate.
[0015] Furthermore, in step (S2), the weight ratio of each material in the printing slurry is 70-90 parts of the first powder: 5-25 parts of the photosensitive resin mixed liquid: 0-2.5 parts of the suspending agent: 0.1-2 parts of the first foaming agent: 5-20 parts of the second powder: 0.1-2 parts of the anti-sticking agent: 0.1-1.5 parts of the second foaming agent.
[0016] Furthermore, in step (S2), the first powder and the photosensitive resin mixed solution obtained in (S1) are mixed and ball-milled in a ball mill until uniform, and then transferred to a mixer for stirring. The ball-milling mixing is a conventional operation in the art.
[0017] Further, in step (S2), the first powder is at least one of alumina, diaspore or kaolin; preferably, the alumina is γ-Al2O3 with a particle size of 10-25 μm; the particle size of diaspore is 10-25 μm; the particle size of kaolin is 0.5-2 μm. Further, in step (S2), a pore-forming agent can be added, and the pore-forming agent can be one or more of carboxymethyl cellulose and starch; the weight of the pore-forming agent accounts for 0.3%-3.0% of the first powder.
[0018] Furthermore, in step (S2), the suspending agent is one or more of sodium bentonite, lithium bentonite or attapulgite, preferably sodium bentonite.
[0019] Further, in step (S2), the first foaming agent and the second foaming agent are each independently selected from a weakly acidic or alkaline water-soluble high-foaming detergent; preferably, the foaming agent is an alkaline water-soluble high-foaming detergent; preferably, the alkaline water-soluble high-foaming detergent is at least one of hydrogen peroxide or sodium bicarbonate powder; more preferably, the alkaline water-soluble high-foaming detergent is sodium bicarbonate powder.
[0020] Furthermore, in step (S2), the anti-sticking agent is at least one of silicone powder, stearate, paraffin or silicone release agent; preferably, the anti-sticking agent is stearate; more preferably, the anti-sticking agent is magnesium stearate.
[0021] Further, in step (S2), the second powder includes phosphate; preferably, the second powder includes phosphate and an auxiliary agent, wherein the weight ratio of the phosphate to the auxiliary agent is 20:1-5:1. Further, the phosphate is at least one of sodium phosphate or disodium hydrogen phosphate, and the auxiliary agent is at least one of cerium oxide or calcium carbonate.
[0022] Furthermore, the phosphate includes sodium phosphate and disodium hydrogen phosphate at the same time, wherein the weight ratio of sodium phosphate to disodium hydrogen phosphate is 1:1-1:10, preferably 1:2-1:10.
[0023] Furthermore, the auxiliary agent includes cerium oxide and calcium carbonate, wherein cerium oxide and calcium carbonate have a synergistic effect in improving the mechanical strength of the catalyst, the formaldehyde conversion rate and the selectivity of 3-methyl-3-butene-1-ol. Further, the weight ratio of cerium oxide to calcium carbonate is 10:1-1:15, preferably 2:1-1:2.
[0024] Further, in step (S2), the first powder and the photosensitive resin mixed liquid are mixed, the suspending agent and the foaming agent are added, the mixture is subjected to low-speed stirring and vacuum dehydrogenation, the second powder is added, the mixture is subjected to high-speed stirring and vacuum dehydrogenation, the mixture is allowed to stand, the anti-adhesive agent and the foaming agent are added, the mixture is subjected to high-speed stirring and vacuum dehydrogenation, and the printing slurry is obtained. The low-speed stirring and high-speed stirring are both conventional operations in the art.
[0025] Furthermore, in step (S2), the second powder is firstly ball-milled and mixed uniformly in a ball mill and then transferred to a mixer for stirring. The ball-milling mixing is a conventional operation in the art.
[0026] Furthermore, in step (S2), the standing is carried out under normal pressure for a standing time of 8-24 hours.
[0027] Furthermore, in step (S2), the printing slurry is printing slurry or printing paste.
[0028] Further, in step (S3), first import the printing model file and set the printing parameters in the computer of the printer, then load the prepared printing slurry into the liquid carrier, initialize the printing platform and the optical machine, and adjust the slurry surface level; based on the printing scheme set by the target model, the printing slurry is laid layer by layer as a 3D printing raw material, scraped flat with a scraper, and selectively exposed layer by layer using an ultraviolet laser or a DLP-UV light source (365nm-405nm), and the solid base catalyst semi-finished product is obtained after the slurry is cured. Further, the post-processing includes cleaning and sintering. Further, the post-processing is to use compressed gas to blow off the shallow paste of the printed catalyst semi-finished product, and then use an ultrasonic 40-60℃ warm water bath for deep cleaning, an oven 80-120℃ drying for 1-5h, and a muffle furnace for degreasing and sintering to obtain a solid base catalyst. Wherein, the degreasing sintering carried out in the muffle furnace has a sintering temperature of 550-650℃ and a holding time of 2-8h.
[0029] The second aspect of the present invention provides a catalyst for synthesizing 3-methyl-3-butene-1-ol prepared by the above method.
[0030] Furthermore, the mechanical strength of the catalyst is 20-120 N / cm, and more preferably 25-40 N / cm.
[0031] Furthermore, the catalyst has a three-dimensional rectangular grid skeleton structure, wherein the catalyst has a height of 2-12 mm, a length of 2-12 mm, a width of 2-12 mm, and a porosity of 21.5%-95.1%.
[0032] Furthermore, in the catalyst, the basic unit grid skeleton structure of the three-dimensional rectangular grid skeleton structure is a rectangular skeleton structure, preferably a cube skeleton structure, the side length of the basic unit grid skeleton structure is 200-800 μm, and the diameter of the cross section of the skeleton is 50-600 μm.
[0033] Furthermore, in the catalyst, the cross-section of the skeleton of the three-dimensional rectangular grid skeleton structure is preferably rectangular, square or circular, and more preferably circular.
[0034] Furthermore, in the catalyst, in the three-dimensional rectangular grid skeleton structure, the basic unit grid skeleton structure is the same.
[0035] The third aspect of the present invention provides a method for synthesizing 3-methyl-3-butene-1-ol, comprising: reacting formaldehyde and isobutylene under the catalysis of the above-mentioned catalyst to obtain 3-methyl-3-butene-1-ol.
[0036] Furthermore, the reaction conditions include: reaction pressure of 4-10 MPa, reaction temperature of 170-260°C.
[0037] Furthermore, the reaction conditions also include: a mass ratio of formaldehyde to isobutanol of 0.05-0.3, and a mass ratio of catalyst to formaldehyde of 0.05-0.3.
[0038] Compared with the prior art, the present invention has the following advantages:
[0039] In the prior art, the extrusion molding process is commonly used for catalyst preparation, but the mechanical strength of the catalyst produced by the extrusion molding process is not high (5-20N / cm). The inventors have found through research that the use of 3D printing technology and the simultaneous control of the composition and proportion of the printing slurry to prepare a monolithic catalyst with a three-dimensional rectangular grid skeleton structure can effectively improve the mechanical strength of the catalyst and further increase the service life of the catalyst. It is applied to the process of generating 3-methyl-3-butene-1-ol from isobutylene and formaldehyde, and the formaldehyde conversion rate and 3-methyl-3-butene-1-ol selectivity are significantly improved.
[0040] The present invention adopts 3D printing technology to prepare a three-dimensional rectangular grid skeleton structure catalyst, and the auxiliary agent and phosphate, and further between CaCO3 and CeO2, promote each other in improving the formaldehyde conversion rate, 3-methyl-3-butene-1-ol selectivity and pressure intensity. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the basic unit cubic skeleton structure in the catalyst of the embodiment of the present invention. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is described in detail below in conjunction with embodiments.
[0043] In the present invention, the formaldehyde conversion rate and the selectivity of the product 3-methyl-3-butene-1-ol are obtained by gas chromatography. The concentrations of the raw material formaldehyde and the product 3-methyl-3-butene-1-ol are determined by configuring standard curves of different concentrations (since a large amount of solution does not participate in the reaction, it is assumed that the volume before and after the reaction remains unchanged).
[0044] In the present invention, the mechanical strength is measured using a DLIII intelligent particle strength tester, and the average value (in N) is taken after 10 tests, and the average value is divided by the length of the cross section of the catalyst particle (in cm), which is the mechanical strength in N / cm.
[0045] In the present invention, the calculation formulas for conversion rate, selectivity and number of recyclable times are:
[0046] Formaldehyde conversion rate % = (1-n 甲醛产物 / n 甲醛原料 )×100%;
[0047] 3-Methyl-3-butene-1-ol selectivity % = n 3-甲基-3-丁烯-1-醇 / n 甲醛 ×100%;
[0048] Recyclable times N: Nth formaldehyde conversion rate ≥ 1st formaldehyde conversion rate × 90%;
[0049] Among them, n 甲醛产物 represents the number of moles of formaldehyde generated by the reaction, n 甲醛原料 Indicates the number of moles of formaldehyde added to the reaction, n 3-甲基-3-丁烯-1-醇 represents the number of moles of 3-methyl-3-butene-1-ol produced by the reaction, n 甲醛 Indicates the number of moles of formaldehyde consumed in the reaction.
[0050] In the present invention, in each catalyst preparation process, the ball mill speed is set to 40-180r / min at low speed, the stirrer speed is set to 500r / min at low speed, the stirrer speed is set to 1500-2000r / min at high speed, and the vacuum is 0.5-2kPa.
[0051] In the present invention, each catalyst has a three-dimensional rectangular grid skeleton structure, wherein the length of the catalyst is 4 mm, the width is 4 mm, and the height is 5 mm. The basic unit constituting the three-dimensional rectangular grid skeleton structure has a cube skeleton structure, whose side length is 300 μm, and the skeleton cross section is circular with a diameter of 240 μm. The porosity of the catalyst is 50%.
[0052] [Example 1]
[0053] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0054] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O and Na2HPO4·12H2O, 5 and 15 parts by weight, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), high-speed stirring is uniformly carried out, and vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and mixing, vacuumization is evacuated to obtain a printing slurry;
[0055] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model (three-dimensional rectangular grid skeleton structure), using the above-prepared printing slurry as the 3D printing raw material to lay layer by layer, scrape it flat with a scraper, and use ultraviolet laser or DLP-UV light source to selectively expose layer by layer, and after the slurry is cured, a solid base catalyst semi-finished product is obtained;
[0056] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0057] [Example 2]
[0058] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0059] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O, Na2HPO4·12H2O and CaCO3, with weight parts of 4.6, 13.8 and 1.6, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0060] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0061] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0062] [Example 3]
[0063] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0064] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of a second powder (Na3PO4·12H2O, Na2HPO4·12H2O and CeO2, with weight parts of 4.6, 13.8 and 1.6, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0065] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0066] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0067] [Example 4]
[0068] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0069] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 parts by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of a second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, with weight parts of 4.6, 13.8, 1.0 and 0.6, respectively; ball milling and mixing treatment is performed in a ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0070] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0071] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0072] [Example 5]
[0073] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0074] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, with weight parts of 3.5, 14.0, 1.0 and 1.5, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), high-speed stirring is uniformly carried out, vacuumization is carried out, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and mixing, vacuumization is carried out to obtain a printing slurry;
[0075] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model (three-dimensional rectangular grid skeleton structure), using the above-prepared printing slurry as the 3D printing raw material to lay layer by layer, scrape it flat with a scraper, and use ultraviolet laser or DLP-UV light source to selectively expose layer by layer, and after the slurry is cured, a solid base catalyst semi-finished product is obtained;
[0076] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0077] [Example 6]
[0078] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0079] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose having a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, in weight parts of 2.0, 16.0, 1.0 and 1.0, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0080] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model (three-dimensional rectangular grid skeleton structure), using the above-prepared printing slurry as the 3D printing raw material to lay layer by layer, scrape it flat with a scraper, and use ultraviolet laser or DLP-UV light source to selectively expose layer by layer, and after the slurry is cured, a solid base catalyst semi-finished product is obtained;
[0081] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0082] [Example 7]
[0083] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of ethoxylated trimethylolpropane triacrylate, 3 parts by weight of 3-glycidyloxypropyltrimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (in a weight ratio of 1:15) are stirred in a blender to obtain a photosensitive resin mixture;
[0084] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, with weight parts of 4.6, 13.8, 1.0 and 0.6, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), high-speed stirring is uniformly carried out, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and mixing, vacuumization is evacuated to obtain a printing slurry;
[0085] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model (three-dimensional rectangular grid skeleton structure), using the above-prepared printing slurry as the 3D printing raw material to lay layer by layer, scrape it flat with a scraper, and use ultraviolet laser or DLP-UV light source to selectively expose layer by layer, and after the slurry is cured, a solid base catalyst semi-finished product is obtained;
[0086] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0087] [Example 8]
[0088] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of ethyl 4-dimethylaminobenzoate and 2,4-diethylthioxanthone (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0089] (S2) 80 parts by weight of the first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of the above-obtained photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of the second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, with weight parts of 4.6, 13.8, 1.0 and 0.6, respectively; ball milling and mixing treatment is performed in the ball mill for 3 hours in advance), high-speed stirring is uniformly carried out, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and mixing, vacuumization is evacuated to obtain a printing slurry;
[0090] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model (three-dimensional rectangular grid skeleton structure), using the above-prepared printing slurry as the 3D printing raw material to lay layer by layer, scrape it flat with a scraper, and use ultraviolet laser or DLP-UV light source to selectively expose layer by layer, and after the slurry is cured, a solid base catalyst semi-finished product is obtained;
[0091] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0092] [Example 9]
[0093] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0094] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of a second powder (Na3PO4·12H2O, Na2HPO4·12H2O, CaCO3 and CeO2, with weight parts of 4.6, 13.8, 1.5 and 0.1, respectively; ball milling and mixing treatment is performed in a ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0095] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0096] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0097] [Comparative Example 1]
[0098] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0099] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 parts by weight of NaHCO3 powder are added, and after being stirred at a low speed and uniformly in the blender and then vacuumized, 20 parts by weight of a second powder (CaCO3; previously subjected to ball milling and mixing treatment in a ball mill for 3 hours) are added, and after being stirred at a high speed and uniformly in a vacuumized state, the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after being stirred at a high speed and uniformly in a vacuumized state, a printing slurry is obtained;
[0100] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0101] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0102] [Comparative Example 2]
[0103] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0104] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 parts by weight of NaHCO3 powder are added, and after being stirred at a low speed and uniformly in the blender and then vacuumed, 20 parts by weight of a second powder (CeO2; previously subjected to ball milling and mixing treatment in a ball mill for 3 hours) are added, and after being stirred at a high speed and uniformly in a vacuum, the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after being stirred at a high speed and uniformly in a vacuum, a printing slurry is obtained;
[0105] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0106] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0107] [Comparative Example 3]
[0108] (S1) 24 parts by weight of acrylic acid, 12 parts by weight of acrylate (the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is 2:1), 3 parts by weight of 3-glycidyloxypropyl trimethoxysilane, 4 parts by weight of polydimethylsiloxane, and 0.4 parts by weight of a mixture of triethanolamine and methyl o-benzoylbenzoate (the weight ratio is 1:15) are stirred in a blender to obtain a photosensitive resin mixed solution;
[0109] (S2) 80 parts by weight of a first powder (diaspore and carboxymethyl cellulose with a particle size of 10-25 μm, in a weight ratio of 40:1) and 12 parts by weight of a photosensitive resin mixed solution are subjected to ball milling and mixing treatment in a ball mill for 5 hours, and then transferred into a blender, 1 part by weight of sodium bentonite and 0.3 part by weight of NaHCO3 powder are added, and after low-speed stirring and uniform mixing in the blender, vacuumization is evacuated, and then 20 parts by weight of a second powder (Na3PO4·12H2O, Na2HPO4·12H2O, Ca3(PO4)2 and CeO2, with weight parts of 4.6, 13.8, 1.0 and 0.6, respectively; ball milling and mixing treatment is performed in a ball mill for 3 hours in advance), and after high-speed stirring and uniform mixing, vacuumization is evacuated, and the mixture is allowed to stand at normal pressure for 10 hours, and finally 0.2 parts by weight of magnesium stearate and 0.5 parts by weight of NaHCO3 powder are added, and after high-speed stirring and uniform mixing, vacuumization is evacuated to obtain a printing slurry;
[0110] (S3) importing the printing model file into the computer of the printer, setting the printing parameters, loading the above-prepared printing slurry into the liquid carrier, initializing the printing platform and the optical machine, and adjusting the slurry surface level; according to the printing scheme set by the target model, using the printing slurry as the 3D printing raw material for layer-by-layer laying, scraping with a scraper, and selectively exposing layer by layer using an ultraviolet laser or a DLP-UV light source, and obtaining a solid base catalyst semi-finished product after the slurry is cured;
[0111] The printed solid base catalyst semi-finished product was blown off the shallow layer of paste with compressed gas, and then deeply cleaned with ultrasonic warm water bath at 40°C, dried in an oven at 100°C for 1 hour, and degreased and sintered in a muffle furnace (sintering temperature 560°C, insulation time 3 hours) to obtain a three-dimensional rectangular grid skeleton structure catalyst.
[0112] Table 1 Mechanical strength of the catalyst obtained in each example
[0113] Example No. Mechanical strength (N / cm) Example 1 26.1 Example 2 28.7 Example 3 29.5 Example 4 30.6 Example 5 32.6 Example 6 33.9 Example 7 25.4 Example 8 26.7 Example 9 24.5 Comparative Example 1 16.1 Comparative Example 2 17.4 Comparative Example 3 27.3
[0114] Catalyst evaluation
[0115] The evaluation conditions are as follows: 2.4 g of the catalyst obtained in each example, 13.5 g of paraformaldehyde, and 80 g of isobutanol were placed in a 500 mL autoclave, sealed, and nitrogen was introduced to remove the air in the autoclave. The isobutylene metering pump was turned on, the isobutylene feed amount was controlled to be 320 g, the reaction temperature was controlled to be 220 ° C, the reaction pressure was controlled to be 8.0 MPa, the reaction was continued for 4 hours, and the remaining isobutylene and catalyst were removed. After the reaction, the sample was analyzed by gas chromatography to obtain the formaldehyde conversion rate and the selectivity of 3-methyl-3-butene-1-ol. The result data are all average results under this condition, see Table 2.
[0116] Table 2 Evaluation results of the catalysts obtained in each case
[0117]
[0118] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for synthesizing 3-methyl-3-butene-1-ol, comprising: (S1) mixing acrylic acid, acrylate, dispersant, leveling agent and photocuring agent to obtain a photosensitive resin mixed solution; (S2) mixing the first powder and the photosensitive resin mixed solution obtained in step (S1), adding a suspending agent, a first foaming agent and a second powder in sequence, letting the mixture stand, and then adding an anti-sticking agent and a second foaming agent to obtain a printing slurry; (S3) loading the printing slurry obtained in step (S2) into a liquid carrier, performing 3D printing according to a set program, and post-processing to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that: In step (S1), the weight ratio of each substance in the mixed solution is: 20-32 parts of acrylic acid: 8-20 parts of acrylate: 2-10 parts of dispersant: 1.5-7.5 parts of leveling agent: 0.2-2 parts of light curing agent.
3. The preparation method according to claim 1 or 2, characterized in that: In step (S1), the acrylate is one or more of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, dipentaerythritol hexaacrylate, ditripropylene glycol diacrylate, trimethylolpropane triacrylate or ethoxylated trimethylolpropane triacrylate, preferably one or more of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate or trimethylolpropane triacrylate, and more preferably includes both dipropylene glycol diacrylate and trimethylolpropane triacrylate, wherein the weight ratio of dipropylene glycol diacrylate to trimethylolpropane triacrylate is preferably 1-2.5:1-1.
5.
4. The preparation method according to claim 1 or 2, characterized in that: In step (S1), the dispersant is one or both of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane, preferably 3-glycidyloxypropyltrimethoxysilane; And / or, in step (S1), the rheological agent is one or both of polydimethylsiloxane and polymethylsiloxane, preferably polydimethylsiloxane.
5. The preparation method according to claim 1 or 2, characterized in that: In step (S1), the photocuring agent is one or both of a photosensitizer or a photoinitiator, preferably including both a photosensitizer and a photoinitiator, wherein the weight ratio of the photosensitizer to the photoinitiator is preferably 1:10-1:100; And / or, the photosensitizer is one or more of ethyl 4-dimethylaminobenzoate, triethylamine, ethyl-p-dimethylaminobenzoate or triethanolamine, preferably one or more of triethylamine or triethanolamine; And / or, the photoinitiator is one or more of 2-isopropylthioxanthone, methyl o-benzoylbenzoate, 2,4-diethylthioxanthone or 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methyl-1-propanone, preferably one or more of 2-isopropylthioxanthone or methyl o-benzoylbenzoate.
6. The preparation method according to claim 1, characterized in that: In step (S2), the weight ratio of each material in the printing slurry is 70-90 parts of the first powder: 5-25 parts of the photosensitive resin mixed solution: 0-2.5 parts of the suspending agent: 0.1-2 parts of the first foaming agent: 5-20 parts of the second powder: 0.1-2 parts of the anti-sticking agent: 0.1-1.5 parts of the second foaming agent.
7. The preparation method according to claim 1 or 6, characterized in that: In step (S2), the first powder is at least one of alumina, diaspore, and kaolin; Optionally, a pore-forming agent is further added in step (S2), wherein the pore-forming agent is one or more of carboxymethyl cellulose and starch; And / or, the weight percentage of the pore-forming agent is 0.3%-3.0% of the first powder; And / or, in step (S2), the suspending agent is one or more of sodium bentonite, lithium bentonite or attapulgite, preferably sodium bentonite; And / or, in step (S2), the first foaming agent and the second foaming agent are each independently selected from a weakly acidic or alkaline water-soluble high-foaming detergent, preferably an alkaline water-soluble high-foaming detergent; the alkaline water-soluble high-foaming detergent is at least one of hydrogen peroxide or sodium bicarbonate powder, preferably sodium bicarbonate powder; And / or, in step (S2), the anti-sticking agent is at least one of silicone powder, stearate, paraffin or silicone release agent, preferably stearate, and more preferably magnesium stearate.
8. The preparation method according to claim 1 or 6, characterized in that: In step (S2), the second powder includes phosphate; Preferably, the second powder comprises phosphate and an auxiliary agent, the weight ratio of the phosphate to the auxiliary agent is 20:1-5:1; the phosphate is at least one of sodium phosphate or disodium hydrogen phosphate, and the auxiliary agent is at least one of cerium oxide or calcium carbonate; Preferably, the phosphate includes sodium phosphate and disodium hydrogen phosphate, wherein the weight ratio of sodium phosphate to disodium hydrogen phosphate is 1:1-1:10, preferably 1:2-1:10; Preferably, the auxiliary agent includes cerium oxide and calcium carbonate at the same time, wherein the weight ratio of cerium oxide to calcium carbonate is 10:1-1:15, preferably 2:1-1:
2.
9. The preparation method according to claim 1, characterized in that: In step (S3), the post-processing includes using compressed gas to blow off the shallow layer of paste on the printed catalyst semi-finished product, then using ultrasonic 40-60°C warm water bath for deep cleaning, 80-120°C drying for 1-5h, and 550-650°C degreasing and sintering for 2-8h.
10. A catalyst for synthesizing 3-methyl-3-butene-1-ol obtained by the preparation method according to any one of claims 1 to 9.
11. The catalyst according to claim 10, characterized in that: The mechanical strength of the catalyst is 20-120 N / cm; And / or, the catalyst is in a three-dimensional rectangular grid skeleton structure, wherein the catalyst has a height of 2-12 mm, a length of 2-12 mm, a width of 2-12 mm, and a porosity of 21.5%-95.1%; Preferably, in the catalyst, the basic unit grid skeleton structure of the three-dimensional rectangular grid skeleton structure is a rectangular skeleton structure, preferably a cube skeleton structure, the side length of the basic unit grid skeleton structure is 200-800 μm, and the diameter of the cross section of the skeleton is 50-600 μm.
12. A method for synthesizing 3-methyl-3-butene-1-ol, comprising: Formaldehyde and isobutylene are reacted under the catalysis of any one of the catalysts described in claims 10-11 to obtain 3-methyl-3-butene-1-ol.
Citation Information
Patent Citations
Catalyst for synthesizing 3-methyl-3-buten-1-ol and preparation method and use of catalyst
CN109317212A
Composite modified molecular sieve catalyst and preparation method and application thereof
CN111068754A
Flaky alpha-Al2O3 powder and preparation method thereof
CN105731509A
Synthetic method of 3-methyl-3-buten-1-ol, catalyst and preparation method of catalyst
CN107930686A
Method for manufacturing ceramic filter for casting based on photocuring 3D printing technology
CN114394848A
Cited By
Precious metal catalyst based on additive manufacturing and preparation method thereof
CN122098549A